Numerical simulation of flow through suspended and submerged canopy. (May 2019) - Cheng, Wenwan; Sun, Zhaochen; Liang, Shuxiu
Abstract: Aquatic vegetation and marine aquaculture structures construct different forms of canopy. The existence of canopies produces drag resistance to water flow, alters ambient hydrodynamic and ecological environment. This work presents a numerical model to simulate flow through suspended and submerged canopies incorporating the interaction between the fluid field and the vegetation or structures. The numerical model is established based on Reynolds Average Navier–Stokes equations with additional canopy drag terms. Turbulence is modeled using two-equation k  − ε model which takes into account the effect of canopies by an approximation of dispersive fluxes using the drag force produced by the canopy. The plant stem deformation and drag resistance are simulated accounting for both internal and external forces. An empirical formula for the bulk drag coefficient of the canopy region involving the shelter effect is proposed based on numerical simulation and laboratory experiment calibration. The numerical model is validated with existing data from field observation and laboratory experiments.